Knowledge, attitude, practice and associated factors of oxygen therapy among health professionals in Ethiopia: A systematic review and meta-analysis. - Zewdu Bishaw Aynalem; Mekides Nigusu Abera; Birhaneslasie Gebeyehu Yazew; Melsew Dagne Abate; Ayalew Kassie; Fentahun Meseret; Ahmed Nuru Muhamed; Gebremeskel Kibret Abebe; Meseret Mekuriaw Beyene; Tilahun Degu Tsega (PLoS ONE)
Background Oxygen therapy is a life-saving intervention used in various healthcare settings to maintain adequate tissue oxygenation while minimizing cardiopulmonary work. Its effective and safe administration depends largely on the knowledge, attitudes, and practices of health professionals. However, there are no pooled studies that examined these skills in the context of Ethiopia. Therefore, this study aimed to assess the pooled prevalence of health professionals' knowledge, attitude, practice, and determinant factors about oxygen therapy in Ethiopia. Methods The databases PubMed, Web of Science, Scopus, Hinari, Science Direct, African Journal of Online, and Google Scholar were used to search for published studies; Direct Google searches and institutional repositories were used to search for unpublished studies. Duplicate studies were eliminated with Endnote X8 and reported according to PRISMA guidelines. The quality of the included studies was assessed using the Joanna Briggs Institute critical appraisal checklist. A random-effects model was used to estimate the pooled prevalence of KAP among health professionals. Heterogeneity was assessed using Cochran's Q test and I2 statistics. Publication bias was checked by visual inspection of a funnel plot and Egger's regression test. STATA version 11 software was used for statistical analysis. Results A total of 14 studies with 2,960 participants for knowledge and practice and 9 studies with 1,991 participants for attitude were used to estimate the pooled prevalence of KAP among health professionals. The pooled prevalence of good knowledge, positive attitude, and good practice regarding oxygen therapy were 52.13% (95% CI: 43.88, 60.39), 55.08% (95% CI: 50.80, 59.35%), and 48.94% (95% CI: 41.14, 56.74) respectively. Both good knowledge and positive attitude were affected by the availability of oxygen therapy guidelines, with adjusted odds ratios (AOR) of 6.11 (95% CI: 2.45, 15.22) and 2.17 (95% CI: 1.39, 3.39) respectively. Additionally, good knowledge (AOR: 4.31, 95% CI: 1.53, 12.11), training (AOR: 4.09, 95% CI: 2.04-8.20), and having an adequate oxygen supply and delivery system (AOR: 3.12, 95% CI: 1.92-5.07) were statistically associated with good practice. Conclusion and recommendations The national pooled prevalence of good knowledge, positive attitude, and good practice among health professionals was low. Therefore, thorough monitoring, supervision, and evaluation of their oxygen therapy is highly recommended for all stakeholders. Yet again, we strongly advise that the identified factors be improved by organizing training sessions, making oxygen therapy guidelines available, and maintaining an adequate oxygen supply system. Trial registration The review protocol was registered in the international prospective register of systematic reviews with registration number PROSPERO: CRD42023486036.